Bioplastic made from seaweed polysaccharides with green production methods. Issue 5 (October 2021) - Lim, C.; Yusoff, S.; Ng, C.G.; Lim, P.E.; Ching, Y.C.
Abstract: This study aims to analyze the practicability of forming seaweed films and their viability of enhancing the bioplastic market using new green technologies. Seaweeds can form films either directly or using their derivatives like agar, carrageenan, and alginate. Seaweeds films that are formed directly without chemical treatment are a promising approach but currently, the field is still new and more research are needed. Seaweeds have numerous advantages compared to other biomass, where they do not need pesticide or wide land use while can grow fast, easy to harvest, and cheap. Seaweeds can also be mixed with other seaweed species or materials to improve their characteristics and properties. Hence, using seaweeds as biomass material is a promising approach to replace conventional plastic that can not only contribute to the economy but also eco-friendly. Green production methods are more viable to produce seaweed films compared to conventional extraction methods as they are more eco-friendly and economic. This paper will review the green production methods and seaweeds to select the right options for bioplastic production. Graphical Abstract: ga1 Highlights: Bioplastics can be made from raw seaweeds instead of using their derivatives. Green production methods like EAE, MAE, PSE, SFE, UAE, REX, and PBE can improve the production of seaweed bioplastics. Different types of films can be produce with different methods from seaweeds.